A Review on Medication Synchronization Programs in Community Pharmacies to Improve Medication Adherence (Indian Journal of Forensic Medicine & Toxicology, 2021)
Adherence to the prescribed medications plays an important role in treatment of chronic diseases.Hypertension, Ischemic heart diseases, Diabetes mellitus, Dyslipidaemia’s are major health challenges of21st Century and are more expensive. A total 79% of Projected deaths are caused due to chronic diseasesin developing countries. Non adherence to prescribed medications is one of major health threat worldwide.Patients who are on chronic diseases are offen visits multiple health care practioners, numerous pharmacies,and who take multiple drugs results in medication non-adherence. The new primary care models suggestthat there is no promotion of close physician-patient-pharmacist relationships. Training for the treatmentof chronic diseases is seldom satisfactory and there is inadequate consistency and communication betweenhealth care providers. Among health care profession community pharmacist are the ideal position to assistthe management of patients with chronic disease. The Synchronization services are offered by severalcommunity pharmacies to improve medication adherence. These programs work by overcoming the barriersof medication non adherence by refilling their prescription in their single visits. Although there are Numerousmedication synchronization programs are available in community pharmacies effectives of medicationsynchronization programs are confined to its type synchronization programs implemented.